Additional file 1 of Chromosome-length genome assembly and structural variations of the primal Basenji dog (Canis lupus familiaris) genome - Richard J. Edwards (7949342); Matt A. Field (10315270); James M. Ferguson (8360901); Olga Dudchenko (4599463); Jens Keilwagen (230589); Benjamin D. Rosen (6793109); Gary S. Johnson (9620981); Edward S. Rice (10315273); La Deanna Hillier (10315276); Jillian M. Hammond (10315279); Samuel G. Towarnicki (5937779); Arina Omer (10315282); et al. (2021)
Additional file 1: Supplementary Fig. 1. The workflow used to construct the de novo genomes. Supplementary Fig. 2. KAT kmer analysis of China assembly. Supplementary Fig. 3. Identification of putative regulatory elements in basenji’s genome using whole-genome bisulphite sequencing. Supplementary Fig. 4. Predicted copy number of BUSCO Complete genes for three dogs based on long-read read depth. Supplementary Fig. 5. CanFam_Bas nuclear mitochondrial DNA (NUMT) coverage. Supplementary Fig. 6. Comparative short read mapping and single nucleotide variant calling for 58 dog breeds versus three reference genomes: CanFam_Bas, CanFam_GSD (GSD) and CanFam3.1 (BOX).